Regulatory properties of adenosine triphosphate-l-methionine S-adenosyltransferase of rat liver - Lombardini, J. B. (1973)
1. Double-reciprocal plots of the reaction velocity of yeast, rat liver and Escherichia coli ATP-l-methionine S-adenosyltransferases (EC 2.5.1.6) as a function of the l-methionine concentrations (under saturating ATP conditions) demonstrate downward deflexions from linearity for the yeast and E. coli adenosyltransferases and an upward deflexion for the rat liver enzyme. 2. The activities of partially purified preparations of rat liver ATP-l-methionine S-adenosyltransferase are enhanced by low concentrations of non-substrate analogues of l-methionine [e.g. 1-aminocyclopentanecarboxylic acid (cycloleucine) and l-2-amino-4-hexynoic acid], or by inorganic tripolyphosphate, an ATP analogue. When the concentrations of these analogues were raised further, the activity decreased. Double-reciprocal plots became linear in the presence of these modifier analogues. The inhibitions are common to all the l-methionine adenosyltransferases examined, but the activation(s) were only found with rat and mouse liver enzymes and not with enzymes obtained from several other tissues of these or other species. 3. The rate of formation of S-adenosyl-l-methionine bears a sigmoidal relation to the l-methionine concentrations when ATP is saturating. The activating effects of the l-methionine analogues and of tripolyphosphate are observed at low l-methionine concentrations, and become obliterated as the l-methionine concentration is raised. These findings are analysed in terms of various regulatory enzyme models.